PENGEMBANGAN KAPASITAS ORGANISASI BADAN KEPEGAWAIAN DAERAH DI KABUPATEN DELI SERDANG1 - Wardianto Wardianto (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2007)
The variable in this research is the organization capacity of Deli Serdang Local Civil Service Agency. The research employs qualitative approach and descriptive analysis method. The research aims at exploring possible approaches to developing the organization capacity of Deli Serdang Local Civil Service Agency. The research result shows that 3 out of 8 indicators stay within ‘good category’. The other 5 comprising of facilities and infrastructure, work procedures, human resource, finance, and incentive system, are positioned within ‘insufficient category’ for promoting roles and functions of Deli Serdang Local Civil Service Agency. Thus, there are two suggestions Deli Serdang Local Civil Service Agency may take into action to develop its organization capacity: first, improving facilities and infrastructures through procurement, borrowing from other local agencies with excessive facilities, or imploring to the third party; second, reducing work / service chains of command in order to accelerate public service delivery.